Thermalization and dynamical spectral properties in the quark-meson model - Shen, Linda; Berges, Jürgen; Pawlowski, Jan M.; Rothkopf, Alexander (Physical review, 2020)
We investigate the nonequilibrium evolution of the quark-meson model using two-particle irreducible effective action techniques. Our numerical simulations, which include the full dynamics of the order parameter of chiral symmetry, show how the model thermalizes into different regions of its phase diagram. In particular, by studying quark and meson spectral functions, we shed light on the real-time dynamics approaching the crossover transition, revealing, e.g., the emergence of light effective fermionic degrees of freedom in the infrared. At late times in the evolution, the fluctuation-dissipation relation emerges naturally among both meson and quark degrees of freedom, confirming that the simulation approaches thermal equilibrium.
Gesehen am 06.08.2020